2009
DOI: 10.1093/cvr/cvp229
|View full text |Cite
|
Sign up to set email alerts
|

A new transmyocardial degradable stent combined with growth factor, heparin, and stem cells in acute myocardial infarction

Abstract: We have demonstrated in a pig model that an intramyocardial stent implanted with slow release of bFGF, heparin, and BMSC transplantation may significantly increase LV function, cardiac blood flow, and vascular density. Therefore, the present study may provide a new method for the surgical treatment of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…On the other hand, most studies have focused on the short-term effects of BMSC transplantation (14)(15)(16)(17)(18)(19)(20), and studies on medium and long-term effects are few (21). Intramyocardial injection of MSCs has been demonstrated to be safe in large animal models (5,11), and in the present study, 6 months following intramyocardial injection of Flk1 + CD34 + CD3 -BMSCs, SPECT detection indicated that the myocardial filling defect was reduced and LV ejection fraction was significantly improved in AMI models injected with BMSCs compared with uninjected models. Histopathological examination indicated that the area covered by the myocardial infarction and the percentage of cells undergoing apoptosis were reduced; and the percentage of survived myocardial tissue and the vessel densities were augmented, following BMSC injection (P<0.05, compared with controls).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most studies have focused on the short-term effects of BMSC transplantation (14)(15)(16)(17)(18)(19)(20), and studies on medium and long-term effects are few (21). Intramyocardial injection of MSCs has been demonstrated to be safe in large animal models (5,11), and in the present study, 6 months following intramyocardial injection of Flk1 + CD34 + CD3 -BMSCs, SPECT detection indicated that the myocardial filling defect was reduced and LV ejection fraction was significantly improved in AMI models injected with BMSCs compared with uninjected models. Histopathological examination indicated that the area covered by the myocardial infarction and the percentage of cells undergoing apoptosis were reduced; and the percentage of survived myocardial tissue and the vessel densities were augmented, following BMSC injection (P<0.05, compared with controls).…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of transmyocardial channel, bFGF, and heparin anticoagulated degradable stent has already been described in our earlier report [8]. In this study, each stent contained 15 mg of recombinant human bFGF (molecular mass 17.4 kDa, purity > 97%, R&D) and 25 mg of heparin (150 U/mg, Dingguo, Beijing, China).…”
Section: Preparation Of Transmyocardial Channel Bfgf and Heparin Anmentioning
confidence: 98%
“…Isolation, culture, immunophenotype analysis, and labeling of MSCs MSCs were isolated and cultured using the methods described earlier [8]. Immunophenotyping analysis was done by using the methods described earlier [11,12].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric immunophenotyping was performed by using methods as our previously reported [18][19][20]: 5×10 5 cells were suspended with trypsin and were washed 2 times in phosphatebuffered saline (PBS). After centrifugation, the cells were incubated with primary against human CD44, CD29, CD34, and CD90 antibodies for 30 min at 4°C.…”
Section: Bmsc Preparation and Injectionmentioning
confidence: 99%